Opportunities for utilization of non-conventional energy sources for biomass pretreatment. (January 2016) - Singh, Rawel; Krishna, Bhavya B.; Kumar, Jitendra; Bhaskar, Thallada
Highlights: Use of γ, microwave, electron beam can be effectively employed for pretreatment. Selective cleavage is possible using non-conventional methods for pretreatment. Less inhibitory by-products with non-conventional pretreatment methods. Pre-processing of biomass for pretreatment is less cumbersome. Abstract: The increasing concerns over the depletion of fossil resources and its associated geo-political issues have driven the entire world to move toward sustainable forms of energy. Pretreatment is the first step in any biochemical conversion process for the production of valuable fuels/chemicals from lignocellulosic biomass to eliminate the lignin and produce fermentable sugars by hydrolysis. Conventional techniques have several limitations which can be addressed by using them in tandem with non-conventional methods for biomass pretreatment. Electron beam and γ (gamma)-irradiation, microwave and ultrasound energies have certain advantages over conventional source of energy and there is an opportunity that these energies can be exploited for biomass pretreatment.